Impaired verbal communication - research in the post cerebrovascular accident - Daniel Bruno Resende Chaves; Alice Gabrielle de Souza Costa; Ana Railka Souza de Oliveira; Viviane Martins Silva; Thelma Leite de Araujo; Marcos Venícios de Oliveira Lopes (Rev Rene)
One of the most common sequelae in people with Cerebrovascular accident, and that affect the quality of life of the patients, is the alteration in communication. The study aimed at investigating the prevalence of the nursing diagnosis Impaired Verbal Communication in patients with stroke in the rehabilitation phase. It is an exploratory cross-sectional study, conducted in two rehabilitation institutions in Fortaleza, CE, Brazil. 40 patients were assessed in the period March-April, 2008. Impaired verbal communication was found in 15 participants (37.5%). The change in speech represented by the diagnosis Impaired Verbal Communication is an alteration present among the patients affected by stroke who were enrolled in this study. The change in speech is an important sequela, one which deserves more attention and preparation of the nurses to provide specific care to people in this condition.